Curd-Peptide Based Novel Hydrogel Inhibits Biofilm Formation, Quorum Sensing, Swimming Mortility of Multi-Antibiotic Resistant Clinical Isolates and Accelerates Wound Healing Activity - Manna, Sounik; Ghosh, Ananta K.; Mandal, Santi M. (Frontiers in Microbiology, 2019)
Search for a bioactive natural antibacterial agent including wound healing properties is a common practice for the development of new generation molecules. Antimicrobial peptide is a good alternative to antibiotics and easy to form hydrogels in self-assembled condition without pH adjustment. To aim in mind, the peptide pool was extracted from a formulated curd comprising a blend of probiotic bacteria such as Streptococcus thermophillus, Lactobacillus casei, and Bifidobacterium bifidum at optimized ratio of 7:1:2. The water content of curd was collected by the drainage column, centrifuged, filtered through 0.45 µM filter and used for hydrogel preparation. MALDI TOF/TOF MS analysis confirmed the presence of peptides pool in the extracted water. The prepared hydrogel was freeze dried and its effect was subsequently verified on biofilm formation, swarming mortality, antimicrobial, wound healing and biocompatibility. TEM and SEM images revealed the fibrous network of peptides after self-assembled with nonpolar n-hexane solvent and porous structure after drying, respectively. The observed biocompatibility, antimicrobial activity and strong wound healing activity of developed curd based hydrogel have opened a new platform for antibacterial ointment formulation.